A New Event Builder for CMS Run II. Issue 8 (December 2015) - Albertsson, K; Andre, J-M; Andronidis, A; Behrens, U; Branson, J; Chaze, O; Cittolin, S; Darlea, G-L; Deldicque, C; Dobson, M; Dupont, A; Erhan, S; et al.
Abstract: The data acquisition system (DAQ) of the CMS experiment at the CERN Large Hadron Collider (LHC) assembles events at a rate of 100 kHz, transporting event data at an aggregate throughput of 100GB/s to the high-level trigger (HLT) farm. The DAQ system has been redesigned during the LHC shutdown in 2013/14. The new DAQ architecture is based on state-of-the-art network technologies for the event building. For the data concentration, 10/40 Gbps Ethernet technologies are used together with a reduced TCP/IP protocol implemented in FPGA for a reliable transport between custom electronics and commercial computing hardware. A 56 Gbps Infiniband FDR CLOS network has been chosen for the event builder. This paper discusses the software design, protocols, and optimizations for exploiting the hardware capabilities. We present performance measurements from small-scale prototypes and from the full-scale production system.